English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

use implicit differentiation to find an equation of the tangent line to the curve at the given point.

2007-10-07 07:24:22 · 2 answers · asked by yakov59 1 in Science & Mathematics Mathematics

2 answers

2/3x^(-2/3) +y' 2/3y^-2/3 =0
y' = [-2/3x^(-2/3)]/ 2/3y^(-2/3)
y' = (-y^2/3)/x^2/3
y' = -1/(-3sqrt(3))^2/3 = 1/3
y = x/3+b
1 = -3*rt(3)/3 + b
b = 1+sqrt(3)
y = x/3 +1+sqrt(3)

2007-10-07 07:40:18 · answer #1 · answered by ironduke8159 7 · 0 20

x^2/3 + y^2/3 = 4

differentiating

2/3 x^(-1/3) + 2/3y^(-1/3) y' = 0

x^(-1/3) = - y^(-1/3)y'

y' = -(y/x)^1/3)

point of tangency = -3sqrt(3), 1

slope = -1/(-3sqrt(3)^1/3

= 1/sqrt(3)

equation of tangent

y-y1 = m(x-x1)

y - 1 = 1/sqrt(3)(x+ 3 sqrt(3)

sqrt(3)[y-1] = x + 3 sqrt(3)

y sqrt(3) - sqrt(3) = x + 3sqrt(3)

y sqrt(3) = x +4 sqrt(3)

divide by sqrt(3)

y =[ x/sqrt(3)] + 4

2007-10-07 07:40:59 · answer #2 · answered by mohanrao d 7 · 15 0

fedest.com, questions and answers